2015
DOI: 10.1002/anie.201505498
|View full text |Cite
|
Sign up to set email alerts
|

Inside Cover: Energetic Insight into the Formation of Solids from Aluminum Polyoxocations (Angew. Chem. Int. Ed. 32/2015)

Abstract: In polluted streams aluminum‐based amorphous solids (flocs) are formed via an intermediate, the ε‐Keggin [AlO4Al12(OH)24(H2O)12]7+ ion (Al137+). In their Communication on A. Navrotsky et al. show the ε‐Keggin Al137+ ion is energetically close to these aluminum flocs. Shown is a stream polluted with aluminum hydroxide flocs from Collar Gulch, Montana. Artwork design by Sharon Betterton, background photograph courtesy of Prof. Chris Gammons, Montana State University.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Aluminum (Al) is the most abundant metal in Earth’s geological environment, and research on Al chemistry plays an important part in the fields of geoscience, water and soil environments, and ecology. A variety of Al species exist, including solute molecules (Al monomers, Al polymers) and hydroxide precipitates (e.g., gibbsite), among which the ε-isomer Keggin AlO 4 Al 12 (OH) 24 (H 2 O) 12 7+ (ε-K Al 13 7+ ) polymer has been demonstrated thermodynamically to be a crucial intermediate species in the transformation of aqueous Al to Al hydroxide precipitates. , With multiple coordinated hydroxyl groups and high charges, the ε-K Al 13 7+ structure includes 12 edge-shared AlO 6 octahedra in four sets of triple linked trimers around a central AlO 4 tetrahedron. , The ε-K Al 13 7+ polymer has been detected in watersheds polluted by mine drainage and acid rain , and has a toxicity that is rather general and more virulent to plants and fishes than Al monomers. Previous studies have reported that ε-K Al 13 7+ is a crucial component for mineral paragenesis and dissolution, as well as for sorption reactions at the solid–water interface, , which regulate the transformation of ions in the geochemical environment.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum (Al) is the most abundant metal in Earth’s geological environment, and research on Al chemistry plays an important part in the fields of geoscience, water and soil environments, and ecology. A variety of Al species exist, including solute molecules (Al monomers, Al polymers) and hydroxide precipitates (e.g., gibbsite), among which the ε-isomer Keggin AlO 4 Al 12 (OH) 24 (H 2 O) 12 7+ (ε-K Al 13 7+ ) polymer has been demonstrated thermodynamically to be a crucial intermediate species in the transformation of aqueous Al to Al hydroxide precipitates. , With multiple coordinated hydroxyl groups and high charges, the ε-K Al 13 7+ structure includes 12 edge-shared AlO 6 octahedra in four sets of triple linked trimers around a central AlO 4 tetrahedron. , The ε-K Al 13 7+ polymer has been detected in watersheds polluted by mine drainage and acid rain , and has a toxicity that is rather general and more virulent to plants and fishes than Al monomers. Previous studies have reported that ε-K Al 13 7+ is a crucial component for mineral paragenesis and dissolution, as well as for sorption reactions at the solid–water interface, , which regulate the transformation of ions in the geochemical environment.…”
Section: Introductionmentioning
confidence: 99%